2006
DOI: 10.5271/sjweh.1016
|View full text |Cite
|
Sign up to set email alerts
|

Overtime work and its effects on sleep, sleepiness, cortisol and blood pressure in an experimental field study

Abstract: Dahlgren A, Kecklund G, Åkerstedt T. Overtime work and its effects on sleep, sleepiness, cortisol and blood pressure in an experimental field study. Scand J Work Environ Health 2006;32(4):318-327.Objectives Previous studies of long workhours and their effects on stress, sleep, and health show inconclusive results. This inconclusiveness may be partly due to methodological problems such as the use of between-group designs or comparisons before and after reorganizations. In addition, stress is usually a confounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 27 publications
(34 reference statements)
3
59
1
Order By: Relevance
“…Building on the effort-recovery theory (17,18), we can hypothesize that, during the course of the workweek, the need for recovery increases, and this phenomenon may explain why the participants seldom worked overtime on Friday evening. This explanation receives support from a recent study on overtime work among faculty members and other office workers by Dahlgren and her colleagues (32), who found that sleepiness (ie, the need to recover) was stronger at the end of the week. The temporal pattern of overtime work in our study may also partly be explained by commitments in the nonwork area (eg, social events) that are more common on Friday than on Monday.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Building on the effort-recovery theory (17,18), we can hypothesize that, during the course of the workweek, the need for recovery increases, and this phenomenon may explain why the participants seldom worked overtime on Friday evening. This explanation receives support from a recent study on overtime work among faculty members and other office workers by Dahlgren and her colleagues (32), who found that sleepiness (ie, the need to recover) was stronger at the end of the week. The temporal pattern of overtime work in our study may also partly be explained by commitments in the nonwork area (eg, social events) that are more common on Friday than on Monday.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, it can be argued that employees can also work overtime in the mornings before 0900. Previous studies indeed showed that overtime workers can report an earlier start of the workday during overtime periods (32,41). Yet morning overtime work did not seem to be a common phenomenon in our sample, as the average time between waking up in the morning and leaving for work was 84 minutes.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 86%
“…Recently, the effects of overtime on stress reactions were studied by comparing a week of overtime with a normal week within the same group while controlling for workload (114). The results showed that the week with overtime was associated with decreased sleep, more symptoms of fatigue and exhaustion, and an increase in sleepiness at the end of the week.…”
Section: Regulation Of Overtime and Excessive Workhoursmentioning
confidence: 99%
“…As indicated in figure 1, the theoretical model for this study presumed that overtime is associated with negative occupational factors (ie, poor interpersonal relationships, reduced job satisfaction) and unfavorable heath behaviors (ie, short sleep, reduced physical exercise) affecting immune function through intermediary conditions (ie, high depressive symptoms, obesity) consequently leading to physical disorders. Studies have indicated that overtime work is associated with high work-related stress and poor health behaviors (9,23). Poor health behavior such as sleep deprivation and sleep loss is directly connected to a reduction of NK cells and increased inflammatory responses (24)(25)(26)(27) as well as depressed mood, stress symptoms, and obesity (10,28,29).…”
mentioning
confidence: 99%
“…Poor health behavior such as sleep deprivation and sleep loss is directly connected to a reduction of NK cells and increased inflammatory responses (24)(25)(26)(27) as well as depressed mood, stress symptoms, and obesity (10,28,29). Meanwhile, job stress has been shown to exert a negative impact on immune outcomes (30)(31)(32)(33)(34), and nocturnal sleep is known to be disturbed by overtime and job stress (23,(35)(36)(37). Based on this model, our study was undertaken to examine the association between overtime and cell-mediated immune markers, taking the potential mediating factors into account by stepwise analyses.…”
mentioning
confidence: 99%